Economic Potential Development of Home Industries in Gunung Tanjung District, Tasikmalaya Regency - Alfauzan, Fauzi; Marjan, Imam; Fatika, Fedora Firda; Dzaqiah, Meila Nazwa; Abidin, Sindy Ardianty; Agnia, Siti Ardianty; Astuti, Yani Sri; Indrianeu, Tineu (Jurnal Pendidikan Geografi Unpatti, 2023)
This study aims to find a problem (1) in the marketing of bananas. (2). Where the development of home industry industry (3) in the village tanjungsari does not go smoothly. The management economy that began to decline due to pandemic factors resulted in this banana sale marketing decreased. The industrial home in the village of Tanjungsari was initially a place to make the income of the community. This industrial home has a huge influence on the well-being of the surrounding communities. The existence of this industrial home has a huge challenge: market access and lack of product promotion that causes sales to decline. This banana industry must have a new strategy in dealing with this. This marketing needs the help of the society era 5.0 (4) that can help in such marketing through millennials and generation z (5). Qualitative research is a research process to understand human or social phenomena by creating a comprehensive and complex picture that can be presented in words, reporting detailed views obtained from informing sources, and performed in a natural setting.